From ‘Consensus Theory of Truth’ to ‘Janus-Faced’ Truth — A Research on Jurgen Habermas’s Theory of Truth - Zunpan Zhang; Xiaoling Wu (Studies in Social Science & Humanities, 2024)
It is one of the critical tasks for Jurgen Habermas to figure out the essence of truth. During 1970s, Habermas has established his philosophy framework of ‘universal pragmatics’. Under this framework, Habermas developed his ‘consensus theory of truth’, which explain truth as validity claim that achieve by discourse. But in 1990s, Habermas discarded this comprehend of truth and put forward a theory of ‘Janus-faced’ truth. In his masterpieces during this period, he was committed to hold both the truth of discourse on utterance level and the truth of reality on lifeworld practice level. This is a peculiar viewpoint that differ from both realist like Putnam and pragmatist like Rorty. In other words, it’s an approach between them.